Systems Approach in Modeling Production and Consumption of Peat Products - SEMIN, Alexander; GREVTSEV, Nikolai; EGOSHINA, Olga (Journal of Environmental Management and Tourism, 2018)
The article substantiates the effectiveness of the systems approach in solving tasks of rational nature management in the integrated development of peat resources. The effectiveness of applying the end-to-end energy-ecological analysis of peat production modes is theoretically substantiated and experimentally confirmed, taking into account energy costs and environmental impact by minimizing technological fuel and technological environmental numbers as comprehensive process indicators. A three-level topological model of the peat products production and consumption system is proposed, which includes the following subsets: “Raw resources”, “Raw materials extraction and processing” and “Graded peat fuel consumption”. Technological fuel numbers (TCH) and technological environmental numbers (TEC) are calculated at each level within the framework of an end-to-end energy-ecological analysis. This calculation allows for a comprehensive analysis, assessment of the enterprise efficiency in terms of environmental pollution damage. The algorithm for selection of technology and composition of peat products is considered in the article. This algorithm utilizes the calculated technological fuel-ecological number (TTEC) for the purpose of the integrated assessment of energy-ecological costs for production in kg of fuel equivalent/t of products. Knowledge of TTEC helps make a choice in favor of certain formulations of the technological mixture, production technologies and properties of the finished product. Based on the systems approach, it is possible to interlink the solution of various tasks – technical, engineering, ecological, economic, information, and organizational ones. The proposed model of the peat products production and consumption system is of practical importance and serves as one of the prerequisites for increasing output and expanding the range of peat composite products due to the selection of optimal technology and composition.